Risk factors for early graft detachment requiring rebubbling in Descemet membrane endothelial keratoplasty with imported pre-cut donor tissues - Kim, Chung Young; Yoon, Chang Ho; Kim, Mee Kum (Frontiers in Medicine, 2024)
Graft detachment is a common and significant complication in Descemet membrane endothelial keratoplasty (DMEK). We investigated the risk factors of graft detachment requiring rebubbling after DMEK using imported pre-cut donor tissues. The medical records of 48 patients who underwent DMEK for Fuchs’ endothelial dystrophy (FED) or bullous keratopathy (BK) at Seoul National University Hospital were retrospectively reviewed. Donor, recipient, and surgical factors were evaluated using univariate and multivariate logistic regression models. Graft detachment requiring rebubbling occurred in 17 (32.7 %) eyes. The detachment group exhibited older recipient age (P=0.006), higher prevalence of diabetes (P=0.001) and a higher proportion of FED (65%, P=0.003). Notably, the detachment group demonstrated a significantly lower postoperative two-hour intraocular pressure (IOP) (P=0.002) and a greater proportion of eyes with IOP <20 mmHg (P<0.001). Older recipient age (OR 1.08, 95% CI 1.02–1.17), diabetes (OR 23.8, 95% CI 2.61-217), FED surgical indication (OR 6.19, 95% CI 1.74–22.0), lower postoperative two-hour IOP (OR 1.21, 95% CI 1.06–1.38), and postoperative two-hour IOP <20 mmHg (OR 14.0, 95% CI 1.64–119) were associated with increased odds of graft detachment. According to multivariate logistic regression, lower postoperative two-hour IOP (OR 1.23, 95% CI 1.02–1.47) and postoperative two-hour IOP <20 mmHg (OR 25.1, 95% CI 1.05–602) increased the risk of graft detachment. Lower postoperative two-hour IOP, particularly below 20 mmHg, may increase the risk of graft detachment, and diabetes in recipients may pose a higher risk of graft detachment after DMEK.